2006
DOI: 10.4161/hv.2.1.2523
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculin Purified Protein Derivative (PPD) Immunoassay as an In Vitro Alternative Assay for Identity and Confirmation of Potency

Abstract: KEY WORDS ABSTRACTTuberculin purified protein derivative (PPD) currently can only be standardised by delayed hypersensitivity skin reactions in sensitised guinea pigs. An in vitro dot blot immunoassay was developed for both identity and confirmation of potency estimation of PPD. Polyclonal antibodies (mainly IgG) were generated and immunoreacted with human, bovine and, to lesser extent, avian PPD preparations. Combining size exclusion chromatography (FPLC-SEC) and dot blot immunoassay, the results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The prolonged heating of crude tuberculin to prepare PPD contributed to the denaturation, par-tial degradation, and aggregation of many of the protein components. Numerous studies identified PPD as mixtures of very heterogeneous proteins ranging in size from very large aggregates to very small degraded molecules (Klausen et al, 1994;Rowland et al, 1999;Ho et al, 2006). Similarly, little was known regarding which of these components in PPD was responsible for the DTH response.…”
Section: Pitfalls Of Ppdmentioning
confidence: 99%
“…The prolonged heating of crude tuberculin to prepare PPD contributed to the denaturation, par-tial degradation, and aggregation of many of the protein components. Numerous studies identified PPD as mixtures of very heterogeneous proteins ranging in size from very large aggregates to very small degraded molecules (Klausen et al, 1994;Rowland et al, 1999;Ho et al, 2006). Similarly, little was known regarding which of these components in PPD was responsible for the DTH response.…”
Section: Pitfalls Of Ppdmentioning
confidence: 99%
“…The proteomic characterization of human and veterinary PPDs has been described by other authors [27,30], showing that PPD contains hundreds of different proteins. In fact, several studies defined PPDs as very heterogeneous compositions of proteins that range in size from very large aggregations to very small degraded segments [25,31,32,33]. In the study of Borsuk et al [27], two bovine PPDs (Brazilian and English) and two avian PPDs (Brazilian and English) were characterized by LC-MS/MS to effectively study their protein profile; a total of 171 different proteins were identified, 77.9% of which was represented by cytoplasmic proteins, while 22.4% was represented by membrane or secreted proteins.…”
Section: Introductionmentioning
confidence: 99%